Study on the morphology stability of TiO2 nanotube arrays towards temperature as a potential toxic gas sensor - Mohd Hasmizam Razali; Muhammad Hafiz Ashraf Mat Zaid; Mahani Yusoff (2016)
TiO2 nanotube arrays were prepared by electrochemical anodization of titanium foil in mixed electrolyte solution of NH4F, water, and glycerol. The anodized TiO2 nanotube arrays were calcined at various temperatures and characterized using scanning electron microscope to study the morphology transformation. The results show that at low calcination temperature (300̊C) highly ordered TiO2 nanotube arrays are observed and remained up to 500̊C. At 700̊C, TiO2 nanotube arrays are completely destroyed and transformed to irregular shaped particle.